Fibrinolysis-treated myocardial infarction in a patient with missed spontaneous coronary artery dissection associated with takotsubo syndrome: case report. Issue 4 (7th December 2018) - Y-Hassan, Shams; Henareh, Loghman
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is an under-recognized acute cardiac disease entity. It is often missed, or misdiagnosed as coronary spasm, coronary atherosclerotic lesion, or thrombotic coronary occlusion. During the last years, SCAD also has been reported to be 'misdiagnosed as takotsubo syndrome (TS)' in patients with features consistent with both conditions. Spontaneous coronary artery dissection may present as an acute coronary syndrome and sometimes as sudden cardiac death. Case summary: We report on the case of a 67-year-old woman who presented with features of ST-elevation myocardial infarction treated with fibrinolysis. The patient showed to have obtuse-marginal SCAD, which was misdiagnosed as fibrinolysis caused lysis of a coronary thrombus. The patient had moreover all other features of TS. Discussion: This case report teaches important information about SCAD. The association between SCAD and TS are discussed.